Research the Fuzzy Controllers in Computer Control Systems - Kovaliuk, Dmytro; Kovaliuk, Oleh; Skladannyy, Denys (2022 IEEE 4th International Conference on Advanced Trends in Information Theory (ATIT), 2022)
The fuzzy model synthesis algorithm is considered and a fuzzy PD-controller is developed on its basis. A comparison of control systems with fuzzy and PID controllers is carried out. Possible variants of fuzzy and PID controllers joint application are analysed. The scheme of their parallel operation with switching depending on the error value is presented. A fuzzy controller, which task is to adjust the coefficients of the PID-controller, is developed. The control system's transient characteristics with the proposed adaptive controller were studied.